2009
DOI: 10.1007/s00034-009-9098-3
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Delayed Chaotic Neural Networks by Periodically Intermittent Control

Abstract: This paper studies the exponential stabilization of delayed chaotic neural networks (DCNNs) using what is called periodically intermittent control. An exponential stability criterion for the controlled neural networks, together with its simplified version, is established by using the Lyapunov function and Halanay inequality. The feasible region of control parameters is estimated in a rigorous way. Theoretical results and numerical simulations show that the continuous-time DCNN can be stabilized by intermittent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
89
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 21 publications
0
89
1
Order By: Relevance
“…Synchronization plays a very important role in many contexts, such as synchronous communication, signal synchronization (for example, synchronization between video and audio signals), firefly bioluminescence synchronization, geostationary satellites, synchronous motors, database synchronization [1][2][3][4][5]. So far, many effective control approaches have been proposed to achieve synchronization, such as adaptive control [6][7], feedback control [8][9], pinning control [10][11], impulsive control [12][13] and intermittent control [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Synchronization plays a very important role in many contexts, such as synchronous communication, signal synchronization (for example, synchronization between video and audio signals), firefly bioluminescence synchronization, geostationary satellites, synchronous motors, database synchronization [1][2][3][4][5]. So far, many effective control approaches have been proposed to achieve synchronization, such as adaptive control [6][7], feedback control [8][9], pinning control [10][11], impulsive control [12][13] and intermittent control [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent control has a nonzero control width, while impulsive control is only activating at some isolated instants. On the other hand, as a special form of switching control, intermittent control can be divided into two classes [16]: state-dependent switching rule and time-dependent switching rule. The former implies that the control operation is activated only when the states enter to a certain region which is often pre-given, while the latter rule activates the control only in some finite time intervals, the system evolving freely outside these intervals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hu et al [22] suggested a pinning synchronization control scheme for a class of linearly coupled neural networks. Huang et al [23] investigated the stabilization of delayed chaotic neural networks by periodically intermittent control. Further, Cai et al [24] considered the outer synchronization between two hybrid-coupled delayed dynamical networks via aperiodically adaptive intermittent pinning control.…”
Section: Introductionmentioning
confidence: 99%